원자력발전소의 부지감시시스템의 운영과 활용 - 박동희(Dong hee Park); 조성일(Sung il Cho); 이용희(Yong Hee Lee); 최원학(Weon Hack Choi); 이동훈(Dong Hun Lee); 김학성(Hak sung Kim) (자원환경지질, 2018)
Nuclear power plants(NPP) are constructed and operated to ensure safety against natural disasters and man-made disasters in all processes including site selection, site survey, design, construction, and operation. This paper will introduce a series of efforts conducted in Korea Hydro and Nuclear Power Co. Ltd., to assure the safety of nuclear power plant against earthquakes and other natural hazards. In particular, the present status of the earthquake, fault, and slope safety monitoring system for nuclear power plants is introduced. A earthquake observatory network for the NPP sites has been built up for nuclear safety and providing adequate seismic design standards for NPP sites by monitoring seismicity in and around NPPs since 1999. The Eupcheon Fault Monitoring System, composed of a strainmeter, seismometer, creepmeter, Global Positioning System, and groundwater meter, was installed to assess the safety of the Wolsung Nuclear Power Plant against earthquakes by monitoring the short- and long-term behavioral characteristics of the Eupcheon fault. Through the analysis of measured data, it was verified that the Eupcheon fault is a relatively stable fault that is not affected by earthquakes occurring around the southeastern part of the Korean peninsula. In addition, it was confirmed that the fault monitoring system could be very useful for seismic safety analysis and earthquake prediction study on the fault. K-SLOPE System for systematic slope monitoring was successfully developed for monitoring of the slope at nuclear power plants. Several kinds of monitoring devices including an inclinometer, tiltmeter, tension-wire, and precipitation gauge were installed on the NPP slope. A macro deformation analysis using terrestrial LiDAR (Light Detection And Ranging) was performed for overall slope deformation evaluation. 원자력발전소는 부지선정, 부지조사, 설계, 건설 및 운영의 전 과정에 걸쳐 지질조사, 단층 및 지진 특성 분석, 탄성파 탐사, 시추조사, 지반특성 분석 등 모든 가능한 지질학적, 지진학적, 지구물리학적 조사와 자료 분석을 통하여 자연재해 및 인위적 재해에 대하여 건전성을 확보할 수 있도록 견고하게 건설, 운영되고 있다. 본 단보에서는 한국수력원자력(주)에서 자연재해에 대해 원자력발전소 부지의 안전성을 평가하기 위하여 구축하여 운영 중인 지진관측시스템, 단층감시시스템, 사면감시시스템 등 일련의 부지감시시스템의 현황 및 주요 관측 자료에 대한 분석결과를 소개하고자 한다. 원자력발전소에는 발전소의 구조물 및 자유장에 여러 대의 가속도계와 지진 트리거로 구성된 지진감시계통을 구성하여 내진설계의 적절성 평가, 지진으로 인한 운전기준 초과 판정, 지진 신속 대응에 활용하고 있다. 이와는 별도로 단층과 지진과의 상관성 분석, 지진발생 특성 연구, 지진재해도 평가 등 원전 부지의 지진안전성 확보를 위하여 1999년부터 원자력 발전소 부지 내 및 인근 지역에 총 13개소의 지진관측소를 운영하고 있으며, 2017년 최신의 지진관측 장비로 교체 설치하였다. 또한 원전 인근의 단층의 활동성을 감시하기 위하여 국내에서 처음으로 체계적으로 단층감시 기반을 확립한 읍천단층 감시시스템(Eupcheon Fault Monitoring System, EFMS)을 2012년 1월부터 운영하고 있다. EFMS는 시추공 변형률계 및 지진계, 지표변위계, GPS, 지하수위계 등으로 구성되며, 상기 계측기의 자료분석 결과 읍천단층은 한반도 동남부 일대에서 발생된 지진에 의해서도 영향을 받지 않는 안정된 단층임을 입증할 수 있었으며, 단층의 지진 안전성 해석과 지진예측 연구에도 단층 감시시스템이 매우 유용하게 활용될 수 있음을 확인하였다. 추가적으로, 2016년부터는 원전 부지 내 사면의 안전성 평가를 위하여 한울원전 배후사면을 대상으로 지중경사계, 지표경사계, 사면변위계, 강우량계 등을 설치하고 K-SLOPE 시스템을 구축하여 사면 거동을 감시하고 있으며, 전체 사면의 거시적 변형거동 평가를 위해 지상 LiDAR를 활용한 분석을 실시하였다. 상기와 같이 한국수력원자력(주)에서는 원자력발전소의 지진 등 자연재해에 대한 부지 안전성 평가를 위하여 실시간 부지 감시기반을 구축, 운영하고 있으며 지속적인 관측자료의 분석기법 고도화, 지진 및 단층과의 상관성 분석, 단층 장기 거통특성예측 기술개발을 통하여 보다 견고하게 원자력발전소의 지진안전성 확보에 기여할 수 있을 것으로 기대된다.